Penerapan Algoritma Apriori Data Mining Untuk Menentukan Penyusunan Layout Barang Pada Toko Ritel - Agung Triayudi (Forum Kerjasama Pendidikan Tinggi, 2022)
Retail is an activity that includes the sale and purchase of goods. For retail stores, the continuity of the business processes that are carried out is very dependent on the sale of goods or the purchase of goods from consumers. Retail stores today must have a strategy or a way to increase sales of their goods. One strategy that can be applied in increasing sales is the preparation of the layout of goods. Errors in the preparation of the layout of goods are of course very detrimental to retail stores, these errors can lead to a stagnant sales process or also decreased sales. The arrangement of the layout of goods can be done by looking at the characteristics of the goods purchased by consumers or commonly referred to as goods associations. Data mining is a technique that can be used to process data. In data mining itself there are many ways that are used to solve problems, one of the ways used to solve problems in data mining is the a priori algorithm. The combination of items obtained by consumers buying item A will also buy Item B with a support value of 20% and a confidence value of 50%. Another combination of items is that consumers buying item A also buys item D with a support value of 10% and a confidence value of 25%. The last combination of item sets, namely Consumers buying item B will also buy item D with a support value of 20% and a confidence value of 50%